The Impact of Compensation and Work Environment on Employee Performance at PT. Samudera Agencies Indonesia - Sudrajat, Moch Agus; Casilam, Casilam (Pascasarjana Universitas Pasundan, 2023)
This study aims to analyze the effect of compensation and work environment on employee performance at PT. Samudera Agencies Indonesia. The focus of this study is to determine whether compensation and work environment partially or simultaneously have a significant effect on employee performance. The research method used is a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to employees of PT. Samudera Agencies Indonesia. The data analysis technique used multiple linear regression tests, t tests for partial effects, and F tests for simultaneous effects, with data processing using SPSS. The results showed that compensation had a significant effect on employee performance with a t count (2.843)> t table (1.998) and a significance of 0.006 <0.05. On the other hand, the work environment did not have a significant effect on employee performance, indicated by t count (0.065) <t table (1.998) and a significance of 0.948> 0.05. However, simultaneously, compensation and work environment had a significant effect on employee performance with F count (12.054)> F table (3.09). These results show that compensation is the main factor in improving employee performance, while the work environment needs to be improved to better support work effectiveness.